The force-velocity profile for jumping: What it is and what it is not - Robbert, M. F.; Lindberg, K.; Bjørnsen, T.; Solberg, P.; Paulsen, G. (Medicine & Science in Sports & Exercise, 2023)
Introduction Force-velocity profiling has been proposed in the literature as a method to identify the overall mechanical characteristics of lower extremities. A force-velocity profile is obtained by plotting for jumps at different loads the effective work as a function of the average push-off velocity, fitting a straight line to the results, and extrapolating this line to find the theoretical maximum isometric force and unloaded shortening velocity. Here we investigated whether the force-velocity profile and its characteristics can be related to the intrinsic force-velocity relationship.